A case of Becker muscular dystrophy with early manifestation of cardiomyopathy - Ki Hyun Doo; Hye Won Ryu; Seung Soo Kim; Byung Chan Lim; Hui Hwang; Ki Joong Kim; Yong Seung Hwang; Jong-Hee Chae (Korean Journal of Pediatrics, 2012)
An 18-year-old boy was admitted with chest discomfort, nausea, and dyspnea at rest. At the age of 3 years, he underwent muscle biopsy and dystrophin gene analysis owing to an enlarged calf muscle and elevated serum kinase level (6,378 U/L) without overt weakness; based on the results, Becker muscular dystrophy (BMD) was diagnosed. The dystrophin gene showed deletion of exons 45 to 49. He remained ambulant and could step upstairs without significant difficulties. A chest roentgenogram showed cardiomegaly (cardiothoracic ratio, 54%), and his electrocardiogram (ECG) showed abnormal ST-T wave, biatrial enlargement, and left ventricular hypertrophy. The 2-dimensional and M-mode ECGs showed a severely dilated left ventricular cavity with diffuse hypokinesis. The systolic indices were reduced, including fractional shortening (9%) and ejection fraction (19%). Despite receiving intensive medical treatment, he died from congestive heart failure 5 months after the initial cardiac symptoms. We report a case of BMD with early-onset dilated cardiomyopathy associated with deletion of exons 45 to 49. Early cardiomyopathy can occur in BMD patients with certain genotypes; therefore, careful follow-up is required even in patients with mild phenotypes of BMD.